Development of Teacher Guidebook for Photoelectric Effects Instructional Using Predict-Observe-Explain Strategy with PhET Interactive Simulation - Siswoyo Siswoyo (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
This study developed a teacher book guide for photoelectric effects instructional using the Predict Observe Explain strategy with PhET interactive simulation. This study used the ADDIE Model consisting of Analysis, Design, Develop, Implementation and Evaluation. The results of the validation component of the graphics feasibility were 91.1 (very feasible), the validation of the content feasibility component was 97.5 (very feasible), and the validation of the instructional feasibility component was 81.7 (very feasible). While the test component of instructional feasibility by the teacher obtained results of 85.9 (very feasible). The results concluded that the teacher book guide for photoelectric effects instructional using the Predict Observe Explain strategy with PhET interactive simulation was declared very feasible to be used as a teacher guidebook.